Effect of Topographical Feature Size on the Trend of Cell Behaviors - Kim, Hong Nam; Kim, Jangho (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2018)
Since the adaptation of surface topography in the biomedical engineering field, its promising ability in the modulation of cell behaviors and functions has been highlighted by comparing the cell behaviors on patterned and nonpatterned substrates. However, growing evidence indicates that not only the topography itself but also its size can significantly affect the cell behaviors and functions. In this review, the effect of topographical feature size on the biointerface-mediated control of cell behavior is overviewed. The cell behaviors such as migration, differentiation, cell reprogramming, cell phenotype, and transfection, in general, showed two representative trends: biphasic and monotonic as the feature size changed. Based on the observations, we suggest that the sophisticated design of geometrical feature size might be a key regulator on the control of cell behaviors and functions.
Keywords: MATRIX NANOTOPOGRAPHY; STEM-CELLS; DIFFERENTIATION; ORIENTATION; PHENOTYPE; SHAPE